Phylogeographic history of Japanese macaques. (15th April 2021) - Ito, Tsuyoshi; Hayakawa, Takashi; Suzuki–Hashido, Nami; Hamada, Yuzuru; Kurihara, Yosuke; Hanya, Goro; Kaneko, Akihisa; Natsume, Takayoshi; Aisu, Seitaro; Honda, Takeaki; Yachimori, Syuji; Anezaki, Tomoko; et al.
Abstract: Aim: Understanding patterns and processes of geographic genetic variation within and among closely related species is the essence of phylogeography. Japanese macaques, also called snow monkeys, have been extensively studied, particularly in the fields of sociobiology, ecology and experimental biology; however, our knowledge of their evolutionary history is relatively limited. In this study we aimed to elucidate the geographic patterns of genetic variation in Japanese macaques and the processes that underlie them. Location: Japan. Taxa: Japanese macaque, Macaca fuscata ; rhesus macaque, M. mulatta ; Taiwanese macaque, M. cyclopis . Methods: Double‐digest restriction site‐associated DNA (RAD) sequencing was used to identify genome‐wide single nucleotide variants. We used fineRADstructure, ADMIXTURE and principal component analyses to estimate the genetic population structure. Phylogenetic relationships were then inferred based on neighbour‐net, neighbour‐joining, maximum likelihood and SVDquartets algorithms. We assessed gene flow using demographic inference and ABBA‐BABA tests, and estimated past distributions during the Last Glacial Maximum (LGM) using ecological niche modelling. Results: Japanese macaques show a sister group relationship with a clade comprising Chinese rhesus, Indian rhesus and Taiwanese macaques. Japanese macaques comprise major north‐eastern and south‐western clades, with a boundary located near central Japan, and gene flow between the north‐eastern and south‐western lineages was detected. Refugia during the LGM were estimated to be distributed in limited areas along the south coasts of the Japanese archipelago. Main conclusions: Phylogeographic variation of Japanese macaques is likely due mainly to northeast–southwest divergence, which resulted from withdrawal into refugia during the glacial period, and subsequent gene flow.